ADVANCEMENTS IN EDUCATIONAL WEB RESOURCE DEVELOPMENT - Abdujabbor Abdurazakov (American Journals, 2023)
With the pervasive integration of contemporary information, communication, and pedagogical technologies, including electronic textbooks and multimedia tools, the educational landscape in the country's schools, vocational colleges, academic lyceums, and higher education institutions is experiencing a profound transformation. This concerted effort aims at a fundamental elevation of educational quality. Central to this endeavour is the strategic enhancement of educational and laboratory infrastructures through the infusion of cutting-edge educational and laboratory equipment, alongside state-of-the-art computer resources. Simultaneously, concerted efforts are directed towards cultivating an effective system aimed at materially and morally incentivizing the dedicated efforts of educators and instructors. This article delves into the intricate process of creating electronic information educational resources. It outlines their diverse types and structural elements while elucidating the stringent requisites for their development. Emphasizing the significance of these resources, the discussion navigates through the nuances of their creation, offering insights into their intricate design and delineating the requisite criteria for their seamless development. The aim is to encapsulate the essence of the article, emphasizing the transformational impact of modern technologies on educational institutions and shedding light on the process and significance of creating electronic information educational resources. Adjustments can be made based on the specific emphasis or details required for your piece.
Keywords: Electronic Textbooks, Multimedia Tools, Educational Technology, Information Resources, Pedagogical Technologies, Educational Infrastructure, Laboratory Equipment, Computer Resources, Teacher Incentives, Educational Quality Enhancement.